Gene expression in gastric biopsies from patients with Helicobacter pylori infection - D. Davoudi Oskouei; H. Akpınar; S. Sarıoğlu; P. Keskinoğlu; M. Soytürk; İ. Şimşek; Ö. Yılmaz (Microbiota in Health and Disease)
Objective: Heterogeneity among Helicobacter pylori (H. pylori) strains in the expression of CagA and outer membrane proteins (OMPs) is an important factor influencing clinical outcomes. We investigated the expression of H. pylori cagA, omp6 (hopA), omp13 (oipA), omp18, and omp20 (alpA) genes and their associations with clinicopathological findings.